1997
DOI: 10.1002/hep.510260214
|View full text |Cite
|
Sign up to set email alerts
|

Role of ischemia in causing apoptosis, atrophy, and nodular hyperplasia in human liver

Abstract: of apoptosis such as portal vein thrombosis (PVT). Portal Ischemia is known to be a cause of hepatocellular apoptosis vein ligation is well-known to cause apoptosis in an experiand atrophy in experimental animals, but the effect of vascular mental model, 1,2 but the association of ischemia and obstruction on such lesions in the normal or cirrhotic human apoptosis has not been reported in human livers.3 liver has not been studied. ity, and acute and healed portal vein thrombosis (PVT). LargeThe effect of porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(66 citation statements)
references
References 22 publications
4
59
1
2
Order By: Relevance
“…Previous studies have indicated that liver angiogenesis is stimulated by inflammation-derived mediators 6,15,23 and by fibrosis-associated hypoxia. 24 Our results showing a significant correlation between the grade of inflammation and serum levels of VEGF also support this concept. Based on this evidence, it seems logical that therapy-induced improvement of the hepatic lesion (that is, resolution of inflammation and regression of fibrosis) could result in inhibition of angiogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have indicated that liver angiogenesis is stimulated by inflammation-derived mediators 6,15,23 and by fibrosis-associated hypoxia. 24 Our results showing a significant correlation between the grade of inflammation and serum levels of VEGF also support this concept. Based on this evidence, it seems logical that therapy-induced improvement of the hepatic lesion (that is, resolution of inflammation and regression of fibrosis) could result in inhibition of angiogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…The results may have direct clinical implications in liver diseases involving portal vein obliteration. Ischemia caused by this condition has been shown to cause hepatocellular apoptosis and liver atrophy in the absence of chronic inflammation [57] …”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, it has been demonstrated that ligation of one branch of the portal vein leads to atrophy of the ischemic portion and hypertrophy of the vascularized region of the liver [11]. In human livers obtained at explant, segmental resection, or autopsy, it has been shown that apoptosis, focal atrophy, and nodular hyperplasia of the liver are associated with acute and healed portal vein thrombosis [12]. The ensuing microcirculatory disturbances at the level of the liver sinusoid appear to occur either due to a mechanical obstruction or functionally due to local hemodynamic changes.…”
Section: Pathogenesismentioning
confidence: 99%